Evaluating the impact of short animated videos on COVID-19 vaccine hesitancy: an online randomized controlled trial - Beleites, Ferdinand; Adam, Maya; Favaretti, Caterina; Hachaturyan, Violetta; Kühn, Tilman; Bärnighausen, Till; Barteit, Sandra (Internet interventions, 2024)
Addressing the global challenge of vaccine hesitancy, amplified during the COVID-19 pandemic due to misinformation propagated via social media, necessitates innovative health communication strategies. This investigation scrutinizes the efficacy of Short, Animated, Story-based (SAS) videos in fostering knowledge, behavioral intent, and engagement around COVID-19 vaccination. We conducted an online three-arm parallel randomized controlled trial (RCT) involving 792 adult participants (≥18 years, English-speaking) from the United States. The intervention group viewed a SAS video on COVID-19 vaccination, the attention placebo control group watched a SAS video on hope, and the control group received no intervention. Our primary objectives were to assess the influence of SAS videos on knowledge, behavioral intent, and engagement regarding COVID-19 vaccination. Participants in the intervention group displayed significantly higher mean knowledge scores (20.6, 95 % CI: 20.3-20.9) compared to both the attention placebo control (18.8, 95 % CI: 18.5-19.1, P < .001) and control groups (18.7, 95 % CI: 18.4-19.0, P < .001). However, SAS videos did not notably affect behavioral intent. Perception of COVID-19 as a significant health threat emerged as a strong predictor for engaging with the post-trial video without further incentives (OR: 0.44; 95 % CI: 0.2-0.96). The 35-44 age group exhibited the highest post-trial engagement (P = .006), whereas right-wing political inclination negatively associated with engagement (OR: 1.98; 95 % CI: 3.9-1.01). Vaccination status correlated significantly with self-efficacy (P < .001), perceived social norms (P < .001), and perceived response efficacy of the COVID-19 vaccine (P < .001), all heightened in the intervention group. These findings suggest that while SAS videos effectively amplify COVID-19 vaccination knowledge, their impact on behavioral intent is not direct. They do, however, affect determinants of vaccination status, thereby indirectly influencing vaccination behavior. The study highlights the appeal of SAS videos among younger audiences, but underscores the need for further examination of factors impeding vaccination engagement. As SAS videos closely mirror conventional social media content, they hold significant potential as a public health communication tool on these platforms. Trial Registration: Trial was registered at drks.de with the identifier DRKS00027938, on 5 January 2022.
IAvailable online 1 December 2023
Gesehen am 30.09.2024